2018
DOI: 10.3389/frobt.2018.00092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dehazing on Underwater Marker Detection for Augmented Reality

Abstract: Underwater augmented reality is a very challenging task and amongst several issues, one of the most crucial aspects involves real-time tracking. Particles present in water combined with the uneven absorption of light decrease the visibility in the underwater environment. Dehazing methods are used in many areas to improve the quality of digital image data that is degraded by the influence of the environment. This paper describes the visibility conditions affecting underwater scenes and shows existing dehazing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The experimental results showed that the new method performed better than original one. In [19], Zuzi used the three dehazing techniques to enhance the underwater images where there were artificial markers. The experimental results showed that SP (Screened Poisson Equation for image contrast enhancement) outperformed the other two enhancement algorithms, BCP (Bright Channel Prior) and ACE (Automatic Color Enhancement), while all of them presented that the marker detection was completed in a shorter time.…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results showed that the new method performed better than original one. In [19], Zuzi used the three dehazing techniques to enhance the underwater images where there were artificial markers. The experimental results showed that SP (Screened Poisson Equation for image contrast enhancement) outperformed the other two enhancement algorithms, BCP (Bright Channel Prior) and ACE (Automatic Color Enhancement), while all of them presented that the marker detection was completed in a shorter time.…”
Section: Related Workmentioning
confidence: 99%
“…The evaluation of circular self-similar markers [32] in open sea environments was presented in [33]. The performance of marker detection and image-improving algorithms was also evaluated by Žuži et al [34] andČejka et al [35] on videos taken in the sea. Several authors focused on the registration of images and based their comparisons on the number of detected and matched SIFT features.…”
Section: Related Workmentioning
confidence: 99%
“…All these conditions are inevitable, and although the progress of underwater camera’s sensors technology together with the knowledge on the capturing process of objects in motion Silvatti et al (2013) can help to reduce some of their effects, adding complexity to the system will always have an impact in the cost of developing any underwater robotic platform. In recent years, the problem of detection and tracking of underwater moving objects has received considerable attention Zuzi et al (2018) ; Panda and Nanda (2020) due to wide applications in oceanographic research. It is clear thus, the need of an autonomous navigation system capable of detecting and tracking underwater moving objects of interest.…”
Section: Introductionmentioning
confidence: 99%